Viruses Like Chickenpox And Shingles Provide Difficulties For Public Health - Jamil, Maryam; David Faijue, Darlington; Iqbal, Robina (Journal of Neonatal Surgery, 2025)
This study aims to assess the epidemiological behaviour of varicella and herpes zoster (HZ) to identify whether or not health policies are required to reduce the prevalence of these diseases and stop complications from occurring. Both the materials and the processes. We analysed data from the National Information System for Epidemiological Surveillance (SUIVE) from 2000 to 2013 to determine the frequency of the occurrences. To evaluate the discharge data of varicella and HZ, we reviewed information from the National System of Health information called Sinais. This is the outcome. A total of 296,733 instances of chickenpox were reported annually, with 57% of those cases occurring in children younger than nine years old and the majority occurring during March and May. The number of patients discharged from hospitals with varicella between 2004 and 2012 was 17,398. Of those patients, 4.6% had meningoectolitis, 2.5% had pneumonia, and 18% had various sequelae. Regarding herpes zoster, there were 7 042 discharges, the majority of patients afflicted were those who were 65 years old or older, and the ratio of females to males was 1.3:1. Neuralgia (17%), eye involvement (7%), meningoencephalitis (5.4%), disseminated disease (2.8%). Other problems (5.4%) were the most common consequences, and the time spent in the hospital ranged from 6.4 to 13.3 days. The final thoughts. These findings are in line with the research that has been conducted in other nations. A discussion is held regarding vaccination's significance in preventing infection in children and adults